Status of the avifauna of San Rafael National Park, one of the last large fragments of Atlantic Forest in Paraguay - Esquivel Mattos, Alberto (2007)
We provide new information on all birds known from San Rafael National Park, Paraguay. Ornithological records from the period 1997 to 2006 have been reviewed, adding 112 new species to the reserve's avifauna. We provide data on the presence of 405 species in seven basic habitats types, and on their relative abundance. Biogeographically, San Rafael has a mixed avifauna, consisting of 70 Atlantic Forest endemic species, two Mesopotamian Grassland endemics, and many with a wider distribution in South America. At least 12 species are threatened and 16 near-threatened, including important populations of Dryocopus galeatus, Platyrinchus leucoryphus, Alectrurus tricolor and Xanthopsar flavus. We provide brief comments on records of these 28 species within the study site. The avifauna of the reserve is one the most important in Paraguay, due to its high diversity and endemism. At the same time, it is under great threat and its viability is at risk unless urgent actions are taken. Fragmentation of the Atlantic Forest in Paraguay has left the San Rafael block almost totally isolated from other forests. The degradation of its forests through selective logging and clearance for agriculture still has severe impacts, as do hunting and frequent fires in grasslands and forests. Unfortunately, the legal situation of the National Park is extremely precarious, creating great uncertainty and problems for its conservation.